The Influence of Academic Leadership on the Effectiveness of Digital Formative Assessment in Improving Student Learning Outcomes in Elementary Schools - Nur Efendi (The Elementary Journal, 2025)
This study examines how academic leadership influences the effectiveness of digital formative assessment in improving student learning outcomes in elementary education. The research was conducted at SDN Salakkembang Tulungagung using a qualitative case study design involving one principal and six teachers selected purposively. Data were collected through semi-structured interviews, classroom observations, and document analysis, then analyzed using thematic analysis. The findings show that academic leadership was enacted through instructional supervision, mentoring, and continuous professional development that strengthened teachers’ capacity in designing and implementing digital formative assessment. Teachers integrated digital tools into daily instruction through interactive quizzes, real-time feedback, and data-informed learning activities. Students demonstrated improved conceptual understanding, increased engagement, and stronger motivation during learning processes. They were able to identify errors, revise their work, and participate actively in assessment activities. The alignment between leadership practices and assessment implementation created a structured, responsive, and student-centered learning environment. The study indicates that academic leadership plays a key role in enhancing the effectiveness of digital formative assessment and improving student learning outcomes in elementary schools.